The Navigation The Landscape of Adult Growth: A Bibliometric Odyssey through Scopus-Indexed Publications on Adult Value Reflection (1972-2023) - Rohmah, Isna Annisa; Mustofa, Triono Ali; Jinan, Mutohharun; Maksum, Muh. Nur Rochim; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine adult learning and self-development mapping in Scopus-indexed publications. This research uses bibliometric analysis techniques to examine all publications indexed in the Scopus database on adult values reflection from 1972 to 2023. The data were analysed using Excel and R/R-Studio. VOSviewer was used to analyze the co-occurrence of keywords and document citations visually. The author found 507 publications matching the defined function, subject, and criteria. The results of this study show an annual growth rate of 7.8%, with the most publications on adult values reflection in 2018. The United States is the country with the highest contribution. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases were not included in this study. This study presents a snapshot of the literature accessible to researchers in the fields of education and health and provides recommendations for future research. Important information about the data.